Peak Edema Extension Distance: An Edema Measure Independent from Hematoma Volume Associated with Functional Outcome in Intracerebral Hemorrhage - Giede-Jeppe, Antje; Gerner, Stefan T.; Sembill, Jochen; Kuramatsu, Joji; Lang, Stefan; Lücking, Hannes; Staykov, Dimitre; Huttner, Hagen B.; Volbers, Bastian (Neurocritical Care, 2023)
Background: Our objective was to test the association between hematoma volume and long-term (> 72 h) edema extension distance (EED) evolution and the association between peak EED and early EED increase with functional outcome at 3 months in patients with intracerebral hemorrhage (ICH). Methods: This retrospective cohort study included patients with spontaneous supratentorial ICH between January 2006 and January 2014. EED, an edema measure defined as the distance between the hematoma border and the outer edema border, was calculated by using absolute hematoma and edema volumes. We used multivariable logistic regression accounting for age, ICH volume, and location and receiver operating characteristic analysis for assessing measures associated with functional outcome and EED evolution. Functional outcome after 3 months was assessed by using the modified Rankin Scale (0–3 = favorable, 4–6 = unfavorable). To identify properties associated with peak EED multivariable linear and logistic regression analyses were conducted. Results: A total of 292 patients were included. Median age was 70 years (interquartile range [IQR] 62–78), median ICH volume on admission 17.7 mL (IQR 7.9–40.2), median peak perihemorrhagic edema (PHE) volume was 37.5 mL (IQR 19.1–60.6), median peak EED was 0.67 cm (IQR 0.51–0.84) with an early EED increase up to 72 h (EED72–0) of 0.06 cm (− 0.02 to 0.15). Peak EED was found to be independent of ICH volume (R 2 = 0.001, p = 0.6). In multivariable analyses, peak EED (odds ratio 0.224, 95% confidence interval [CI] [0.071–0.705]) and peak PHE volume (odds ratio 0.984 [95% CI 0.973–0.994]) were inversely associated with favorable functional outcome at 3 months. Receiver operating characteristic analysis identified a peak PHE volume of 26.8 mL (area under the curve 0.695 [95% CI 0.632–0.759]; p ≤ 0.001) and a peak EED of 0.58 cm (area under the curve 0.608 [95% CI 0.540–0.676]; p = 0.002) as best predictive values for outcome discrimination. Conclusions: Compared with absolute peak PHE volume, peak EED represents a promising edema measure in patients with ICH that is largely hematoma volume-independent and nevertheless associated with functional outcome.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Early EED increase; Edema; EED; ICH; PHE